2022
DOI: 10.1007/s00267-022-01752-2
|View full text |Cite
|
Sign up to set email alerts
|

Oil Infrastructure has Greater Impact than Noise on Stress and Habitat Selection in Three Grassland Songbirds

Abstract: Oil extraction may impact wildlife by altering habitat suitability and affecting stress levels and behavior of individuals, but it can be challenging to disentangle the impacts of infrastructure itself on wildlife from associated noise and human activity at well sites. We evaluated whether the demographic distribution and corticosterone levels of three grassland passerine species (Chestnut-collared Longspur, Calcarius ornatus; Baird’s Sparrow, Centronyx bairdii; and Savannah Sparrow Passerculus sandwichensis) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 68 publications
(110 reference statements)
0
5
0
Order By: Relevance
“…Evaluating stress hormone levels sensu Des Brisay ( 2018 ) of fledglings, juveniles, and adult longspurs in crop sites could provide additional insight into habitat quality. Body condition at the start of migration often influences survival of adults and juveniles during migration and winter (Angelier et al, 2011 ; Labocha & Hayes, 2012 ; Merilä & Svensson, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating stress hormone levels sensu Des Brisay ( 2018 ) of fledglings, juveniles, and adult longspurs in crop sites could provide additional insight into habitat quality. Body condition at the start of migration often influences survival of adults and juveniles during migration and winter (Angelier et al, 2011 ; Labocha & Hayes, 2012 ; Merilä & Svensson, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…This may occur because species find certain features associated with structures attractive, such as perches or additional bare ground. These species may be at risk for ecological traps (Bernath-Plaisted and Koper 2016; Ludlow and Davis 2018; Des Brisay et al 2022). Other species may display no abundance or habitat use response to energy development (e.g., Ludlow et al 2015; Daniel and Koper 2019), but these species may nonetheless suffer demographic consequences.…”
Section: Threats To Grassland Birdsmentioning
confidence: 99%
“…Energy infrastructure can reduce the reproductive success of grassland birds by altering predator communities and/or disrupting the behavior of nesting birds. For example, studies on the effects of oil and gas infrastructure on nesting birds have found decreased nesting success, increased parasitism, elevated stress levels, and reduced parental care ( Bernath-Plaisted and Koper 2016 ;Bernath-Plaisted et al 2017 ;Ng et al 2019 ;Des Brisay et al 2022 ), though others have found few strong effects ( Ludlow et al 2015 ;Yoo and Koper 2017 ). Similarly, documented effects of turbines on nesting success have been mixed with some studies reporting negative responses and others finding no effect ( Hatchett et al 2013 ;McNew et al 2014 ;Mahoney and Chalfoun 2016 ).…”
Section: Anthropogenic Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The road networks and associated infrastructure around well pads are likely to result in greater displacement of grassland birds (Londe et al, 2019; Thompson et al, 2015). Furthermore, the physical infrastructure, increased human activity, and associated noise can negatively affect grassland bird demography by reducing parental care and increasing both physiological stress in adult birds and rates of nest parasitism by brown‐headed cowbirds ( Molothrus ater ; Bernath‐Plaisted & Koper, 2016; Des Brisay et al, 2023; Ng et al, 2019) Since much of the growth in both non‐renewable and renewable fuels is projected to take place in the temperate grassland region of the United States (McDonald et al, 2009), it is important to understand how different sectors of energy development impact grassland ecosystems and wildlife.…”
Section: Introductionmentioning
confidence: 99%